PERILAKU ANOMALI PASAR ATAS AKRUAL KOMFORMITAS AKUNTANSI PAJAK DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia periode 2014-2016) - Nahlatul Janah; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to examine whether there is a market anomaly on theaccrual component of tax accounting conformity in Indonesia. This study uses 98manufacturing companies as samples during the period 2014 - 2016 with a totalof 294 observations. This study uses two pairs of samples as a benchmark todetect the phenomenon of market anomalies marked by mistakes investors inassessing the market and the deviations that may be done by the investors. Thefirst sample pair is the cash flow from operation and the total accrual component.The second pair of samples is the accrual discretion of the accounting conformityof accounting taxes and discretionary accruals. Both are used to detect investors'mistakes in predicting future earnings persistence.The results of this study indicate that the results of tests conducted both onthe difference Cash flow from Operation (CFO) and Total Accruals Component(TAC) as well as on the difference of Accrual conformity Tax Accounting (DTA)and Accounting Accrual Discretion (DBA) can be concluded that there isbehavior of market anomalies which is marked by a market error in assessing thepersistence of future earnings.Keywords: Market Anomaly, Component of Cash Flow, Accrual Component,Accrual conformity Tax Accounting, Accounting AccrualDiscretion.